Diversity and Activity of Sulfate-Reducing Prokaryotes in Kamchatka Hot Springs - Evgenii N. Frolov; Alexandra V. Gololobova; Alexandra A. Klyukina; Elizaveta A. Bonch-Osmolovskaya; Nikolay V. Pimenov; Nikolay A. Chernyh; Alexander Y. Merkel (Microorganisms, 2021)
Microbial communities of the Kamchatka Peninsula terrestrial hot springs were studied using radioisotopic and cultural approaches, as well as by the amplification and sequencing of dsrB and 16S rRNA genes fragments. Radioisotopic experiments with 35S-labeled sulfate showed that microbial communities of the Kamchatka hot springs are actively reducing sulfate. Both the cultivation experiments and the results of dsrB and 16S rRNA genes fragments analyses indicated the presence of microorganisms participating in the reductive part of the sulfur cycle. It was found that sulfate-reducing prokaryotes (SRP) belonging to Desulfobacterota, Nitrospirota and Firmicutes phyla inhabited neutral and slightly acidic hot springs, while bacteria of phylum Thermodesulofobiota preferred moderately acidic hot springs. In high-temperature acidic springs sulfate reduction was mediated by archaea of the phylum Crenarchaeota, chemoorganoheterotrophic representatives of genus Vulcanisaeta being the most probable candidates. The 16S rRNA taxonomic profiling showed that in most of the studied communities SRP was present only as a minor component. Only in one microbial community, the representatives of genus Vulcanisaeta comprised a significant group. Thus, in spite of comparatively low sulfate concentrations in terrestrial hot springs of the Kamchatka, phylogenetically and metabolically diverse groups of sulfate-reducing prokaryotes are operating there coupling carbon and sulfur cycles in these habitats.